Electrical storm in the inflamed heart: ventricular tachycardia due to myocarditis. Issue 8 (3rd July 2017) - Mattsson, Gustav; Magnusson, Peter
Key Clinical Message: Electrical storm during the acute inflammatory phase caused by myocarditis may be resistant to antiarrhythmic therapy. Cardiac imaging including magnetic resonance tomography, positron emission tomography, and endomyocardial biopsy are crucial to guide potential therapeutic options. Optimal management involves a multidisciplinary approach, including expertise beyond cardiology. Abstract : Electrical storm during the acute inflammatory phase caused by myocarditis may be resistant to antiarrhythmic therapy. Cardiac imaging including magnetic resonance tomography, positron emission tomography, and endomyocardial biopsy are crucial to guide potential therapeutic options. Optimal management involves a multidisciplinary approach, including expertise beyond cardiology.